The use of γ-rays analysis by HPGe detector to assess the gross alpha and beta activities in waters - Casagrande, M. F.S. [UNESP] (2018)
This paper describes an alternative method for evaluating gross alpha and beta radioactivity in waters by using γ-rays analysis performed with hyper-pure germanium detector (HPGe). Several gamma emissions related to α and β- decays were used to provide the activity concentration data due to natural radionuclides commonly present in waters like 40K and those belonging to the 238U and 232Th decay series. The most suitable gamma emissions related to β- decays were 214Bi (1120.29 keV, 238U series) and 208Tl (583.19 keV, 232Th series) as the equation in activity concentration yielded values compatible to those generated by the formula taking into account the detection efficiency. The absence of isolated and intense γ-rays peaks associated to α decays limited the choice to 226Ra (186.21 keV, 238U series) and 224Ra (240.99 keV, 232Th series). In these cases, it was adopted appropriate correction factors involving the absolute intensities and specific activities for avoiding the interferences of other γ-rays energies. The critical level of detection across the 186–1461 keV energy region corresponded to 0.010, 0.023, 0.038, 0.086, and 0.042 Bq/L, respectively, for 226Ra, 224Ra, 208Tl, 214Bi and 40K. It is much lower than the WHO guideline reference value for gross alpha (0.5 Bq/L) and beta (1.0 Bq/L) in waters. The method applicability was checked by the analysis of groundwater samples from different aquifer systems occurring in the Brazilian states of São Paulo, Minas Gerais and Mato Grosso do Sul. The waters exhibit very different chemical composition and the samples with the highest radioactivity levels were those associated with lithotypes possessing enhanced uranium and thorium levels. The technique allowed directly discard the 40K contribution to the gross beta activity as potassium is an essential element for humans.